Comparison of the main pathogenic microorganisms of various common oral diseases in children and adults - Siqi Zhou; Tong‐Chuan He; Yuxin Zhang; Hongmei Zhang (Pediatric Discovery)
Abstract The microorganisms in the human body gradually change and maintain a dynamic balance with the development of physiology and pathology. Oral microbiota is one of the most important microbiota in human body. It is not only closely related to the occurrence and development of oral diseases, but also plays an important role in the overall health. In childhood, the population of oral microorganisms is relatively small, but with the growth of age and tooth development, the species and quantity of oral microorganisms are gradually increasing. Different oral diseases also have their corresponding main microorganisms, and these dominant microorganisms change at different stages of the disease. In this review, we summarized and compared the main pathogenic microorganisms of several common oral diseases in children and adults. In addition, the possible association and difference between adults and children of the main pathogenic microorganisms in different stages of the same or different diseases are also discussed in order to provide research data for the development and diagnosis of common oral diseases in children and adults.